O Projeto Professor Diretor de Turma como instrumento de intervenção na formação cidadã. - Andrade, Ana Paula Rodrigues de (2022)
The present work aims to analyze the Teacher Class Director Project (PPDT) in the Public School of the State of Ceará, as an effort to improve pedagogical practices. The class director teacher is an articulator who collaborates with the various school segments, linked to the class he/she coordinates, cooperating with school management. At this stage, the research sought to identify the impacts caused by the Covid-19 pandemic as well as the strategies used by the class director teacher in monitoring the student. The methodology applied was guided by assumptions of qualitative research. We started with the reading and analysis of the PPDT documents, as well as the technique of applying semi-structured interviews. 36 teachers participated in interviews via Google Meet in 2021. The interviews were conducted virtually because of the Covid-19 pandemic. The research results are presented according to the analysis of the data collected in the interview with the teachers, with the school coordinators and with the State Coordination of the project. The reports of the class director teachers highlighted the importance of the Class Director Teacher Project, especially during the Covid-19 pandemic. It was the period in which the teachers contributed to the project of active search for absent students. What was observed with the research work is that the PPDT is an indispensable ally in the development of learning and the promotion of pedagogical practices. However, the testimonies of the class director teachers revealed that the project needs constant reformulations around the new challenges to which the PPDT is subject daily.